2020
DOI: 10.1136/bjophthalmol-2020-317181
|View full text |Cite
|
Sign up to set email alerts
|

Intrasession repeatability and intersession reproducibility of peripapillary OCTA vessel parameters in non-glaucomatous and glaucomatous eyes

Abstract: ObjectiveTo compare intrasession repeatability versus intersession reproducibility of the peripapillary vessel parameters using optical microangiography–based optical coherence tomography angiography (OCTA) in non-glaucomatous and glaucomatous eyes.MethodsIn an observational, longitudinal study, peripapillary OCTA scans were collected to evaluate intrasession repeatability and intersession reproducibility using within-eye coefficient of variation (CVW) and intraclass correlation coefficient (ICC). Images were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…The signal strength is well-known as an important factor when interpreting the OCTA parameters in normal individuals and patients with various retinal diseases. 35 , 36 This study showed that the signal strength was also associated significantly with macular VD in patients with T2DM and patients with T2DM with HTN. Because the OCTA parameters of the macular microvasculature are strongly influenced by the signal strength, physicians should be aware that the comparison of such parameters would be inaccurate if the signal strength is low or different between two tests when analyzing OCTA data for patients with T2DM.…”
Section: Discussionmentioning
confidence: 75%
“…The signal strength is well-known as an important factor when interpreting the OCTA parameters in normal individuals and patients with various retinal diseases. 35 , 36 This study showed that the signal strength was also associated significantly with macular VD in patients with T2DM and patients with T2DM with HTN. Because the OCTA parameters of the macular microvasculature are strongly influenced by the signal strength, physicians should be aware that the comparison of such parameters would be inaccurate if the signal strength is low or different between two tests when analyzing OCTA data for patients with T2DM.…”
Section: Discussionmentioning
confidence: 75%
“…The mean SS (B = − 2.028; p < 0.001) affected long-term repeatability. Previous studies have also identified the SS as an important factor in OCTA evaluations 11 , 14 , 20 23 . Fenner et al 20 reported that motion artifacts and TopQ scores (similar to the SS) could be used to evaluate the quality and reliability of OCTA images.…”
Section: Discussionmentioning
confidence: 95%
“…The sample sizes in these studies were small, and the analyses were limited to calculating the CV. Lee et al 14 reported good long term reproducibility of peripapillary OCTA measurements in 120 individuals with suspicion of glaucoma, using a clinic-oriented quantification software (Cirrus) (CV 2.02% and ICC 0.852 for PD). Although this study did not include healthy eyes, the results are similar to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripapillary OCTA vessel parameters have greater intrasession repeatability than intersession reproducibility in both non-glaucomatous and glaucomatous eyes (7). Previous studies have compared the flow pattern using OCTA in the peripapillary region in normal eyes, glaucomatous eyes, and acute nonarteritic anterior ischemic optic neuropathy (NAION) eyes.…”
Section: Dear Editorsmentioning
confidence: 99%